Corpus-based analysis of three Arabic adversative conjunctions in current Egyptian newspapers - Essa, Shaemaa (AUC Knowledge Fountain, 2013)
Conjunctions function as cohesive and text building elements in Modern Standard Arabic. They play various semantic and discursive roles at different textual levels: phrase, clause, sentence, paragraph and discourse (Al-Batal, 1990). This study investigates the linguistic behavior of three Arabic adversative conjunctions, namely "innam", baynam, and bal. It draws its data mainly from the sub-corpus of Shruq Columns (2,067,137 words) in the Arabicourpus. A random sample has been collected for "innam" and bal, covering 50% of their instances in the corpus. On the other hand, all the instances of baynam with the adversative meaning have been analyzed due to the fact that it does not take on this meaning in the corpus text frequently. The thesis examines the main lexico-grammatical patterns, collocational behavior, and semantic prosody of these conjunctions. The results show that "innam" and bal share some of the lexico-grammatical patterns and collocational behavior, while baynam has its unique patterns. innam and baynam show no clear positive or negative semantic prosody, while one of bal's grammatical patterns has a clear negative semantic prosody. In addition to that, the three conjunctions also have similar collocational behavior. While some phenomena in the behavior of the conjunctions can be attributed to similarities or differences in their meanings, other aspects of their behavior can be understood only through future diachronic investigations. The study ultimately aims at contributing to pedagogical issues concerning the teaching of these conjunctions by providing a more comprehensive picture of their linguistic behavior. Moreover, findings of the current study could contribute to the updating of teaching materials and Arabic Foreign Language writing textbooks.